2016
DOI: 10.1002/ente.201500402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spinel Inversion on (CoxFe1−x)3O4 All‐Oxide Solar Cell Performance

Abstract: Oxide materials have been widely investigated for use as absorber layers in high‐performance solar cells, and in this study combinatorial methods were used to specifically investigate cobalt–iron (Co–Fe) oxide composites. Structural inversion of Co–Fe oxides from a normal to an inverse spinel structure occurs at the critical composition of approximately 33 % Fe added to Co, causing changes in the crystallinity, symmetry, sub‐lattice vibrational modes, optical bandgap, and electrical resistivity. When used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The compositions close to Co 1. 3 are also visible from the 300 nm linear analysis shown in Figure 4d, but cannot be exactly defined at lower scale (i.e. within the column diameter).…”
Section: Tem Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…The compositions close to Co 1. 3 are also visible from the 300 nm linear analysis shown in Figure 4d, but cannot be exactly defined at lower scale (i.e. within the column diameter).…”
Section: Tem Studiesmentioning
confidence: 94%
“…The average Co 1.8 Fe 1.2 O 4 composition deduced from the total spectrum (Figure 6a) is close to the nominal Co 1.7 Fe 1. 3…”
Section: Tem Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…absorber (with TiO 2 as the n-type window layer) resulted in a low PCE of 10 -2 -10 -3 % [282] , [283] . Dopants such as Li, Cu and Fe into the spinel Co 3 O 4 layer has been reported resulting in much enhanced p-type conductivity [284] , [285] , [286] . Patel et al [287] reported that a rapid interfacial layer has a beneficial effect onto the V oc in TiO 2 /Co 3 O 4 /MoO 3 all-oxide solar cells [288] .…”
Section: Otf As the Core: Light Harvestersmentioning
confidence: 99%
“…This was enhanced by 0.6 V by inserting a MoO 3 hole selective layer . Enhanced V OC was also obtained when Co 3 O 4 was doped by Li or Fe . Studies on back metal contacts of Ag, Cu, Ni, and Co for Co 3 O 4 photovoltaics have shown a consistent V OC of 0.4 V .…”
Section: Introductionmentioning
confidence: 95%